Reconfiguration Method Based on DC/DC Central Converter within Different Mismatch Conditions - Hojabri, Mojgan; Ali Mahmood, Humada; Mortaza, Mohamed; Mushtaq, N. Ahmed; M. H., Sulaiman; Mudathir Funsho, Akorede (IJESRT, 2013)
Reconﬁgurable photovoltaic (PV) systems are of great interest with respect to system designers in order to improve the system’s eﬃciency and operation. This paper proposes an adaptive reconﬁguration scheme to reduce the effect of shadows on solar panels. A method to capture the maximum power point of the photovoltaic (PV) array systemwith the help of DC/DC central converter system is presented. The method of connecting the solar adaptive string to the ﬁxed part of the solar photovoltaic (PV) array proposed, which increases the power of the solar PV array according to a model-based algorithm. The model algorithms are implemented in real time. Ideal diode model parameters also proposed for each module in both fixed and adaptive part respectively. The analyses are obtained from the study of the voltage vs. power curve characteristics of the both parts. Finally, the proposed solution is ensuring that the adaptive string has the ability to capture the MPP.